HUBUNGAN INTERNASIONAL DAN HAM DALAM PERSPEKTIF ISLAM - Kamsi Kamsi (Millah: Journal of Religious Studies, 2012)
This paper elaborates international relationship and human rights in the Islamic perspective. The principle of international relations in Islam is an eternal peace that is fundamental rights of every nation, except in an emergency. Then, international relation turns into a war. If war is indeed to be done, the war in Islam is a defending war and does not violate human rights.